Does ignorance of economic returns and costs explain the educational aspiration gap? Representative evidence from adults and adolescents - Lergetporer, Philipp [Verfasser]; Werner, Katharina [Verfasser]; Wößmann, Ludger [Verfasser] (My University, 2021)
“The gap in university enrolment by parental education is large and persistent in many countries. In our representative survey of German adults, 74% of university graduates, but only 36% of those without a university degree, favour university education for their children. The latter are more likely to underestimate returns and overestimate costs of university. Similarly, 75% of adolescents with university-educated parents, but only 51% without university-educated parents aspire to a university degree. Experimental provision of general return and cost information does not close the aspiration gap as treatment effects are at least as strong for individuals with a university background as for those without. Differences in economic preference parameters also cannot account for the educational aspiration gap.” (authors’ abstract; BIBB-Doku)

Knapp drei Viertel der Deutschen mit und gut ein Drittel derjenigen ohne Universitätsabschluss bevorzugen für ihr Kind eine Hochschulausbildung. Unter den Jugendlichen selbst streben 75 Prozent mit, aber nur 51 Prozent ohne akademisch gebildete Eltern einen Universitätsabschluss an. In einer Studie des Ifo Zentrums für Bildungsökonomik wird erläutert, dass diese Lücke in den Bildungsaspirationen durch allgemeine Informationen über Erträge und Kosten eines Studiums nicht geschlossen wird. (BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; P 1.1 Jugendliche; S 1.4 Hochschulbildung; 370; Eltern; Jugendlicher; Bildungsaspirationen; Bildungsentscheidung; Bildungsertrag; Hochschulbildung